Prevention of hand eczema: effect of an educational program versus treatment as usual - results of the randomized clinical PREVEX trial - Maja H Fisker; Niels Erik Ebbehøj; Søren Grove Vejlstrup; Jane Lindschou; Christian Gluud; Per Winkel; Jens Peter Bonde; Tove Agner (Nordic Association of Occupational Safety and Health (NOROSH), 2018)
OBJECTIVE: Occupational hand eczema has adverse health and socioeconomic impacts for the afflicted individuals and society. Prevention and treatment strategies are needed. This study aimed to assess the effectiveness of an educational intervention on sickness absence, quality of life and severity of hand eczema. METHODS: PREVEX (PreVention of EXema) is an individually randomized, parallel-group superiority trial investigating the pros and cons of one-time, 2-hour, group-based education in skin-protective behavior versus treatment as usual among patients with newly notified occupational hand eczema, with follow-up after one year. Co-primary outcomes were total sickness absence, health-related quality of life (HR-QoL), and self-reported severity of hand eczema. RESULTS: Patients (N=1668) with notified occupational skin diseases from July 2012 to November 2014 were invited to participate in the trial. Of these, 756 were randomized to the intervention (N= 376) versus control (N=380) group. The intervention group had 21% fewer sickness absence days compared with the control group [95% confidence interval (CI) -55-40%, P=0.43]. We found no significant difference in the change of HR-QoL for the intervention compared with the control group (4% lower in the intervention group, 95% CI -18-13%, P=0.67). The ordinal odds of scoring worse on self-reported hand eczema severity was 15% lower in the intervention compared with the control group (95% CI -39-18%, P=0.34). Post-hoc sub-group analyses indicated that the effect of the intervention on severity differed between occupations, being detrimental to healthcare workers and beneficial in all other occupations. CONCLUSION: The educational skincare program had no marked effect on the primary outcomes sickness absence, HR-QoL, and severity of hand eczema when compared with treatment as usual.